Is the combination of depression symptoms and multimorbidity associated with the increase of the prevalence of functional disabilities in Brazilian older adults? A cross-sectional study - Rosa, Patrícia Pereira de Souza da; Marques, Larissa Pruner; Corrêa, Vanessa Pereira; De Oliveira, Cesar; Schneider, Ione Jayce Ceola (Frontiers in Aging, 2023)
Introduction: Functional disabilities are more prevalent in older adults with multimorbidity and depression. However, few studies investigate the combination of multimorbidity and depression with functional disability. This study aimed to verify whether symptoms of depression and multimorbidity combined increase the prevalence of functional disability in Brazilian older adults. Material and Methods: This is a cross-sectional study conducted with data from the Longitudinal Study of Brazilian Aging (ELSI-Brazil) baseline, in 2015-16, in adults aged 50 years and older. The variables included were Basic (BADL) and Instrumental Activities of Daily Living (IADL), depressive symptoms, multimorbidity (≥2 chronic diseases), sociodemographics, and lifestyle. Logistic regression was performed to estimate crude and adjusted odds ratios. Results: 7,842 participants over 50 years of age were included. Of those, 53.5% were women and 50.5% were between 50 and 59 years old, 33.5% reported ≥4 depressive symptoms, 51.4% had multimorbidity, 13.5% reported difficulty in performing at least one BADL, and 45.1% in the IADL. In the adjusted analysis, the prevalence of difficulty on BADL was 6.52 (95CI%: 5.14;8.27), and IADL was 2.34 (95CI%:2.15;2.55) higher for those with depression and multimorbidity grouped compared with those without these conditions. Conclusion: The combination of symptoms of depression and multimorbidity may increase functional impairments in the BADL and IADL of Brazilian older adults, impairing self-efficacy, independence, and autonomy. Early detection of these factors benefits the person, their family, and the health care system for health promotion and disease prevention.